2011
DOI: 10.1039/c0cp00146e
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and aggregation properties of dissymmetric phytanyl-gemini surfactants for use as improved DNA transfection vectors

Abstract: Improvements in transfection efficiency are required in order to make the goal of cellular gene delivery by non-viral vectors realizable. Novel derivatives of gemini surfactants having dissymmetric tail groups have been designed specifically as a means to improve DNA transfection; the micelle and interfacial properties are reported herein. The effect of these substitutions on the aggregation properties of the gemini surfactants is discussed in the context of results for the m-3-m gemini series, previously repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 30 publications
2
26
0
Order By: Relevance
“…Different dicationic agents have been explored, with the structure of the head groups and spacers being varied. [36][37][38][39][40][41] To improve the stability and biocompatibility of amphiphile-DNA complexes, cationic surfactant/lipid mixtures have been used or biofragments have been introduced into the surfactant molecules. [42][43][44][45][46][47][48] A perspective approach in gene therapy has been connected with the use of oligonucleotides (ONus) and the development of cationic agents for their delivery.…”
Section: Introductionmentioning
confidence: 99%
“…Different dicationic agents have been explored, with the structure of the head groups and spacers being varied. [36][37][38][39][40][41] To improve the stability and biocompatibility of amphiphile-DNA complexes, cationic surfactant/lipid mixtures have been used or biofragments have been introduced into the surfactant molecules. [42][43][44][45][46][47][48] A perspective approach in gene therapy has been connected with the use of oligonucleotides (ONus) and the development of cationic agents for their delivery.…”
Section: Introductionmentioning
confidence: 99%
“…In order to enhance gene transfection, based upon structure-activity relationship, various gemini surfactants (Gemini surfactants consist of two hydrophobic chains and two polar headgroups linked chemically by a spacer group) have been designed. In order to enhance gene transfection based upon structure-activity relationship, various gemini surfactants have been designed, synthesized and tested for gene delivery in our laboratory (Donkuru et al 2010;Wang and Wettig 2011;Wettig et al 2007a;Wettig et al 2007b;Wettig and Verrall 2001). Recent reports have shown that obstacles can be overcome by exploiting receptormediated endocytosis for highly efficient internalization of ligands naturally employed by eukaryotic cells.…”
Section: Cationic Liposomesmentioning
confidence: 99%
“…The conformation and the biological function of proteins can be modulated by surfactants and, consequently, the ability to control the protein-surfactant interactions is important in applications involving these systems. On the other hand, one of the most extensively studied applications of cationic surfactants regards to their use in gene therapy, as nucleic acid delivery systems [5][6][7]. It is based on the strong attractions between DNA and cationic surfactant aggregates.…”
Section: Introductionmentioning
confidence: 99%